Rho GTPase-related prognostic signature for esophageal squamous cell carcinoma identifies CTTN as a candidate adverse prognostic marker - Hua Chen; Jun-er Xu; Qiancheng Lin; Pingping Dong; Wangkai Xie; Xiangyang Xue; Xiaoming Lin (Molecular Biology Reports, 2026)

A charge and size-switchable Au2Pt nanosystem for deep-tumor penetration and combinatorial therapy of ocular uveal melanoma - Lingdan Kong; Linxin Chen; Pingping Huang; Linghong Wang; Kang Han; Xiaoqian Shi; Yue Zhang; Jizhen Wang; Yunhai Tu; Yuqin Wang; Yong Liu (Chemical Engineering Journal, 2026)

Ligand-induced amorphous and dense interface formation in bone char/Fe(OH)2 hybrid suspension to enhance FeN mediated TCE dehalogenation - Yanhui Yi; Aihua Wei; Pingping Chen; Ning Wang; Jinxin Zhao; Weizhao Yin (Chemical Engineering Journal, 2026)

The N-terminal region of pdm09/H1N1 PA synergizes with its cognate NP to enhance mammalian adaptation of avian-origin H9N2 canine influenza virus - Yefan Zhou; Pingping Wang; Shiqi Li; Fanyuan Sun; Min Zhu; Rang Wang; Shanshan Dong; Haodong Zhang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

The recent process and functional applications of inkjet printing in organic solar cells - Shaomeng Li; Pingping Yang; Miaomiao Zhang; Ziwei Zhao; Zhanwei He; Wenxuan Lv; Haining Chen; Qixian Zhang; Mangmang Gao (Chemical Engineering Journal, 2026)

Multi-omics analysis of the rhizosphere effects and molecular mechanisms of Ageratum conyzoides linn. at different stages of Cd, Pb, and Zn co-stress - Yuexin Fu; Mouyixing Chen; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu; Shaohong You (Journal of Environmental Management, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

The role of polysaccharide ionic character in modulating lubrication behavior of WPI-based composite hydrocolloids - Pingping Tan; Yuanbo Zhong; Zhen Zhang; Wanying Su; Longyang Liang; Jianshe Chen; Ruojun Mu (Food Chemistry, 2026)

Fe-modified tea waste biochar enhances short-term soil organic carbon sequestration: Mechanisms and economic benefit - Weifeng Chen; Huiying Zhang; Yan Wang; Yun Xia; Pingping Lian; Hui Jia; Abdallah Abdelfattahe; Jinzhi Ni; Ran Wei (Environmental Research, 2026)

NS1-A53D enhances HA stability to coordinate viral entry with vRNP export and replication during adaptation of H1N1 canine influenza virus - Min Zhu; Rang Wang; Xiaolong Li; Yefan Zhou; Linying Peng; Pingping Wang; Huabo Zhou; Jianni Huang; Yifeng Qin; Kang Ouyang; Yeshi Yin; Zuzhang Wei; et al. (Veterinary Microbiology, 2026)

Isolation and identification of two causal agents associated with root rot of Scutellaria baicalensis - Lin He; Qianci Chen; Pingping Sun; Lei Zhang; Honghong Jiao; Hongmei Cui; Yuan Yuan; Zhengnan Li (Physiological and Molecular Plant Pathology, 2026)

Dual-mode colorimetric and fluorescent pH sensor based on carbon dots for real-time monitoring of shrimp freshness - Ke Zhang; Pingping Wang; Haiming Chen; Chun Chen; Xiong Fu (Food Packaging and Shelf Life, 2026)

Frequency disentanglement with State space gating network for medical image segmentation - Zuo Huang; Xiang Li; Jinyu Cong; Zhenpeng Chen; Pingping Wang; Benzheng Wei (Medical & Biological Engineering & Computing, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Sediment-associated Rare Earth Elements in an Urban River: Bioavailability and Ecological Risks to Aquatic Biota - Ruijie Peng; Pingping Wu; Zhilin Chen; Junzhuo Cai; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Environmental Processes, 2026)

Ultrasonic degradation of Dendrobium officinale polysaccharide: Kinetics, structural modification, and its impact on wheat starch digestibility - Jinfeng Fu; Xiong Fu; Pingping Wang; Yuxuan Fu; Chun Chen (Food Research International, 2026)

(P)ppGpp synthase Rsh promotes persister cells formation by regulating sulfur metabolism mediated by sulfate reductase CysI in Brucella abortus - Xiaofang Liu; Chenyang Cui; Pingping Wang; Hui Wang; Yunyi Zhai; Yuanhao Yang; Jialu Chen; Wei Liu; Zheng Dong; Dong Zhou; Yaping Jin; Aihua Wang (Veterinary Microbiology, 2026)

Phosphorus limitation drives the deterministic assembly of dissolved organic matter and microbial activity in surface waters of urban lakes - Wei Yu; Pingping Fan; Haiquan Yang; Wenhao Li; Guomin Han; Jifei Hou; Rui Liang; Jingan Chen; Jie Li; Xuede Li (Organic Geochemistry, 2026)

A novel hybrid model for coastal aquaculture ponds integrating hierarchical decision-tree and ensemble-learning approaches from Sentinel satellites - Xiaoyan Yang; Jianqiang Wang; Jian Gao; Pingping Liu; Xingbai Hu; Fei Zhang; Chao Chen (Frontiers in Marine Science, 2026)
Coastal aquaculture ponds represent a significant contributor to economic growth and food provision, underscoring the necessity of precise spatial mapping to support sustainable resource management. Current extraction methods often rely on single-source data and are easily confused by spectral heterogeneity in complex coastal environments, leading to blurred boundaries and misclassification. To overcome these challenges, this study proposes an innovative hybrid model that combines multi-source feature stacking with a hierarchical decision-tree architecture for coarse extraction, followed by an ensemble-learning framework for fine-scale classification. Implemented on the Google Earth Engine cloud platform, the model integrates Sentinel-1 and Sentinel-2 data to leverage complementary spectral, microwave, and terrain features. Applied to the Zhoushan Archipelago in China, the approach produced a high-resolution distribution map of aquaculture ponds with clear boundaries and accurate geolocation. Compared with conventional approaches such as random forest (RF), classification regression trees (CART) and support vector machines (SVM), the proposed model achieved an overall accuracy of 87.34%, improving by 2.55% to 5.39%. The model also achieved a Kappa Coefficient of 73.82% and an F1 score of 89.46%, demonstrating its effectiveness and reliability for automated coastal aquaculture pond extraction in complex coastal environments.

Rational design of fermented mustard tuber quality: Transitioning from empirical processing to precision control via texture-flavor synergy and targeted fermentation strategies - Wenxin Chen; Xiaoli Qin; Pingping Shi; Jinfeng Zhong (Trends in Food Science & Technology, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Effects of phospholipid saturation on cinnamaldehyde liposomes: Structural insights, storage stability, and antioxidant properties - Ting Ding; Xianghua Chai; Pingping Wang; Kegang Wu; Chun Chen; Jing Lin; RouRou Wen; XueJuan Duan (Journal of Food Engineering, 2026)

From lunar terrain to learned representations: A comparative study of crater extraction - Ersa Wei; Xiangmei Liu; Minxuan Gao; Feng Zhang; Pingping Lu; Yanan Dang; Jiahan Wang; Tao Wu; Jiaqi Chen (Icarus, 2026)

18–26 years: A critical window for synergistic reduction of atmospheric pollutant and greenhouse gas emissions - Pingping Song; Zhenhui Gao; Zhiyuan Duan; Junhua Song; Haiyan Duan; Siyan Chen; Bailin He; Meng Gao (Environmental Impact Assessment Review, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Integrating machine learning with NSGA-Ⅱ to assess the synchronization effects of stormwater disaster hazard and green–blue infrastructure - Jiaxuan Chen; Sisi Wang; Pingping Luo; Chong-Yu Xu; Hongyu Zhao (Journal of Hydrology, 2026)

Large spatiotemporal variability in CH4 emissions from a subtropical coastal creek in southeast China affected by hydrological and biogeochemical processes - Lihua Wang; Ping Yang; Yingzi Wang; Pingping Guo; Derrick Y.F. Lai; Kwok Pan Chun; Chuan Tong; Dongyao Sun; Jiafang Huang; Guanpeng Chen; Hong Yang (Journal of Hydrology, 2026)

Microbial generalists and specialists in permafrost demonstrate disparate responses to extreme environments - Chengzhi Mao; Pingping Xu; Ramiro Logares; Bing Ma; Jianchuan Li; Rong Tang; Jiayuan Wang; Xiaosong Wang; Jinglan Wang; Yitong Wang; Yuxiu Chen; Lingyun Chen (Journal of Environmental Management, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

†Trichochterus gen. nov., a new genus of velvety shore bugs from Burmese amber with strong terrestrial adaptation (Insecta: Hemiptera: Ochteridae) - Chunlan Xian; Pingping Chen; Qiang Xie; Yanhui Wang (Cretaceous Research, 2026)

Discovery of an unconventional metabolic pathway within neonicotinoids based on a characteristic fragment-dependent coupled with Cl-specific screening approach - Qianyu Chen; Pingping Kang; Shenghu Zhang; Guanyong Su (Journal of Hazardous Materials, 2026)

Machine learning-based response and prediction analysis for gravity-driven membrane - Pingping Zhang; Zihui Xiao; Yonghao Chen; Shaoqiang Nie; Wenzhong Liang; Wenwei Zhong; Tugui Yuan; Huankai Li; Wenxiang Zhang (Desalination, 2026)

Branch-connected construction of shamrock-shaped giant molecule acceptors enables efficient organic solar cells through optimized molecular architecture - Shanshan Qin; Kangqiao Ma; Jiajia Xi; Fengzhi Wang; Pingping Xi; Hong Huang; Zhenyu Chen; Tao Zhang; Kang Wang; Deping Qian (Chemical Engineering Journal, 2026)

VSIG4 Inhibits Microglia-Mediated Neuroinflammation and Neuronal Injury by Modulating the JAK2-STAT3/NF-κB Signaling Pathway in Parkinson’s Disease - Jingcong Zhuang; Pingping Cai; Zhongjie Chen; Quanlong Hong; Rong Wang; Feng Wang; Yaxin Zhang; Danjie Wu; Fengzhu Chen (Molecular Neurobiology, 2026)

Rational cyclodextrin selection for cinnamon essential oil encapsulation: Performance regulation based on physicochemical characterization and molecular simulation - Jing Lin; Kegang Wu; Pingping Wang; Xuejuan Duan; Jiasi Chen; Ting Ding; Haoyue Xue (Food Chemistry, 2025)

Akkermansia muciniphila and Ruminococcus gnavus dominated mucin-degrading consortia exhibit different effects on intestinal inflammation - Ruocen Tian; Chuan Zhang; Pingping Yin; Shumao Cui; Wenwei Lu; Fengwei Tian; Jianxin Zhao; Qixiao Zhai; Wei Chen (Food Bioscience, 2025)

Ionic covalent organic framework nanosheets modulated polyamide membranes for augmented ion sieving - Rui Li; Meng He; Shuangqiao Han; Linze Li; Pingping Chen; Xiao Wang; Yuping Tong; Jingli Gong; Huixian Wang; Yatao Zhang; Junyong Zhu (Desalination, 2025)

Oligopeptide-loaded metal-organic framework nanocomposites promote regulatory T cell differentiation against periodontitis - Yu Wang; Xiaoqian Gong; Hongli Chen; Pingping Niu; Zhiduo Liu; Yao Sun (Chemical Engineering Journal, 2025)

Prediction of potential habitats of three Coptis species under climate change provides insights on their resource protection and cultivation across China - Pingping Lu; Jieru Chen; Hongting Liu; Xinyue Zhu; Zichun Ma; Xue Huang; Wei Zhang; Hezhong Jiang; Hai Liao; Jiayu Zhou (Environmental Monitoring and Assessment, 2025)

Snow-resilient mapping reveals three decades of surface water expansion on the Qinghai–Tibet Plateau - Shaofan Tang; Yilong Peng; Yongzhi Chen; Jiaming Liu; Pingping Zhang; Ying Zhang; Tingting He; Jianhua Li (Remote Sensing Applications: Society and Environment, 2025)

Unraveling trapped air-suction interplay in hydraulic hysteresis: experimental insights and a state-dependent water retention model - Pingping Sun; Xiaohui Gan; Pan Chen; Maosheng Zhang; Ling Xu; Jun Jia; Mujia Wang (Journal of Hydrology, 2025)

The effect of autophagy activation on apoptosis and myofibrillar structural proteins during the post-mortem storage of Esox lucius - Xuemei Fan; Yibo Liu; Xin Guo; Yabo Wei; Pingping Liu; Hui Li; Xin Chen; Xiaorong Deng; Yongdong Lei; Jian Zhang (Food Chemistry, 2025)

Investigating the Potential of CDDO-Me as an HMGB1 Inhibitor in Mitigating Cerebral Ischemia-Reperfusion Injury - Libang Zhang; Guolong Li; Xingru Chen; Tian Li; Richa Raj; Pingping Shen (Journal of Neuroimmune Pharmacology, 2025)

Spatial metabolomics reveals the effects of Acanthopanax senticosus on region-specific alterations in neurotransmitters and metabolites levels in the brains of α-syn transgenic Parkinson’s disease model mice - Qi Zheng; Yi Lu; Donghua Yu; Liangyou Zhao; Yu Wang; Pingping Chen; Fang Lu; Shumin Liu (Metabolic Brain Disease, 2025)

Coastal creeks as greenhouse gas hotspots: the role of nutrient availability and microbial activity - Guanpeng Chen; Jianuo Gao; Ping Yang; Wenjing Liu; Dongyao Sun; Yongxin Lin; Chuan Tong; Wenjing Tan; Pingping Guo; Hong Yang (Journal of Hydrology, 2025)

Conductive superhydrophobic fabric with dual-induced pH-response for controllable oil-water separation - Xuanjun Li; Xiaojing Su; Junping Liao; Pingping Deng; Zeyuan Lu; Shengye Chen; Kunquan Li; Hongqiang Li; Wenjian Wu (Journal of Environmental Chemical Engineering, 2025)

Multifunctional double-network hydrogel with enhanced interface engineering for high-performance flexible zinc-air batteries - Pingping Xu; Quanchao Zhang; Xingyu Chen; Jie Liu; Naiqin Zhao; Wenbin Hu; Cheng Zhong (Chemical Engineering Journal, 2025)

Characterization of Cyhalofop-butyl metabolism and identification of resistance genes in Barnyardgrass (Echinochloa crus-galli (L.) P. Beauv.) - Penglei Sun; Liangliang Niu; Xianmin Lan; Pingping Chen; Haiyan Yu; Jingchao Chen; Hailan Cui; Xiangju Li (Pesticide Biochemistry and Physiology, 2025)

Optimizing fertilization enhances sustainable vegetable production: combining on-farm composting and biochar application to improve vegetable yield, soil health, and socio-economic benefits - Bihui Tang; Pingping Ye; Xu Luo; Xinyi Yang; Tao Liang; Anle Chen; Duan Yu; Xiaozhong Wang; Ran Xiao (Journal of Cleaner Production, 2025)

A new early warning method for landslide critical sliding tangent angle based on modified Nishihara model - Hui Wu; Pingping Huang; Weixian Tan; Yaolong Qi; Wei Xu; Yuejuan Chen (Engineering Geology, 2025)

Curcumin-based antibacterial waterborne polyurethane/gelatin composite film for pork preservation and freshness indication - Yuye Zhong; Zhenhong Zhang; Zhengjie Chen; Wenshuo Zhang; Xinghai Liu; Pingping Zhao; Tao Zhang; Houbin Li (Chemical Engineering Journal, 2025)

Silk fibroin/collagen hydrogel containing EDIL3 nanoparticles promotes pressure ulcer healing by promoting angiogenesis and remodeling local inflammation - Xuewei Kan; Liwen Luo; Shiyu Zhang; Pingping Yao; Jiaqi Chen; Yuying Jia; Zigang Shen; Zhiqiang Tian; Bing Ni; Jun Tang (Chemical Engineering Journal, 2025)

Effect of split application of nitrogen combined with chitooligosaccharide on lodging in rice - Shuai Yuan; Yuting Su; Pingping Chen; Naimei Tu; Wenxin Zhou; Zhenxie Yi (Plant and Soil, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

Ox-LDL Induces Neuron Apoptosis and Worsens Neurological Outcomes in aSAH via Fas/FADD Pathway - Yabin Song; Chen Yu; Dandan Bo; Junqi Sun; Yong Wang; Pingping Chen; Hanming Wu; Linghong Hong; Zhennan Ye; Long Zhang; Diangui Zhou (Molecular Neurobiology, 2025)

Salcastaniols A-G, seven undescribed diterpenoids with cholinesterase inhibitory activities from Salvia castanea Diels f. tomentosa Stib - Zhaoyue Dong; Pingping Wang; Qingju Liu; Feng Ju; Miaomiao Sun; Mohammad Mahmoud Nagdy; Fancheng Meng; Guowei Wang; Zhihua Liao; Min Chen (Phytochemistry, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Removal of dissolved arsenic from deep seawater around hydrothermal vents and seamounts - Yuanchen Li; Guangyong Bo; Yihua Cai; Kan Zhang; Kuanbo Zhou; Pingping Zhang; Chenjing Yang; Tianyu Chen; Minhan Dai; Jian Ma; Zhimian Cao (Earth and Planetary Science Letters, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Human-induced N-P imbalances will aggravate GHG emissions from lakes and reservoirs under persisting eutrophication - Wei Yu; Fali Liu; Xianglan Jiao; Pingping Fan; Haiquan Yang; Yongmei Zhang; Jie Li; Jingan Chen; Xuede Li (Water Research, 2025)

Divergent invasive and native wetland plant microbial community responses to estuarine wetland salinity gradients - Zongsheng Yuan; Huanhuan Rao; Ziwen Ren; Hao Xue; Yingzi Wang; PingPing Guo; Yongji Huang; Yange Zhang; Zonghua Wang; Songbiao Chen; Yingjiao Zhang (CATENA, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

Synergistic mechanism of magneto-optical sensing mediated by magnetic response protein Amb0994 and LOV-like protein Amb2291 in Magnetospirillum magneticum AMB-1 - Haitao Chen; Changyou Chen; Haoyu Zhao; Yuanyuan Wei; Pingping Wang; Long-Fei Wu; Tao Song (Journal of Photochemistry and Photobiology B: Biology, 2025)

Effects of land consolidation intensity on landscape pattern and biodiversity in paddy ecosystem - Pingping Yang; Minzhu Shen; Yan Zhang; Hao Wang; Yinghao Xue; Baoxiong Chen; Jingjun Bian; Pengyao Li; Ti Zhang; Luyu Wang; Meichun Duan (Agriculture, Ecosystems & Environment, 2025)

Trees show higher resilience than herbs under phosphorus deficit induced by 12‐year simulated acid rain - Guangcan Yu; Mianhai Zheng; Ying‐Ping Wang; Mengxiao Yu; Jun Jiang; Enqing Hou; Nannan Cao; Shu Ye; Songjia Chen; Jingtao Wu; Fengcai Liu; Linhua Wang; et al. (Ecology, 2025)
Acid rain, with 60% deposition in Asia, may exacerbate plant phosphorus (P) limitation; however, its long‐term effects on different plant life‐forms remain largely undetermined. Understanding these effects is essential for predicting ecosystem resilience and promoting forest health under environmental change. Herein, we investigated the P status in two tree and two herb species and their rhizosphere soils after 12 years of acid treatment at three pH levels (pH: 4.0, 3.5, and 3.0) in a tropical forest in Southern China. We found that leaf, litter, and root P; leaf N and P resorption efficiency; and their ratios remained stable in trees; however, herb leaf and litter P levels declined. Acid addition reduced inorganic P in tree rhizosphere soil and inorganic and organic P in herb rhizosphere soil. Rhizosphere soil P fractions were more regulated by soil physicochemical properties and less regulated by microbial community in trees than in herbs. Under long‐term simulated acid rain, stable tree P status benefited from soil inorganic P depletion, and herbs partially met their P requirements via biological mineralization of soil organic P. These distinct P‐associated responses and acquisition strategies provide insights into safeguarding forest health among plants of different functional types under long‐term acid rain events.

Food-derived peptides as novel therapeutic strategies for NLRP3 inflammasome-related diseases: a systematic review - Ziqi Zhang; Yuan Zhang; Meiying Zhang; Chenfeng Yu; Pingping Yang; Minxuan Xu; Jitao Ling; Yuting Wu; Zicheng Zhu; Yixuan Chen; Ao Shi; Xiao Liu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

A nucleocapsid monoclonal antibody based sandwich ELISA for the general detection of both PRRSV-2 and PRRSV-1 - Shaohua Sun; Kaili Zhang; Jiajia Zhang; Ping He; Pingping Zhang; Dafu Deng; Chenglin Chi; Sen Jiang; Wanglong Zheng; Nanhua Chen; Jianzhong Zhu (Veterinary Microbiology, 2025)

The appropriate concentration of L-aspartate nano-calcium promotes growth and potassium utilization in cigar varieties of tobacco (Nicotiana tabacum L.) - Xinying Chen; Naheeda Begum; Dezhi Kong; Yanuo Gong; Munib Ahmad; Pingping Wang; Suiling Ai; Mushtaq Ahmad; Lixin Zhang (Rhizosphere, 2025)

Carboxylated celluloses as effective stabilizers for super-stable Pickering emulsions: Effects of different carboxyl moieties and particle morphologies on performance - Xiaoyun Chen; Feifan Zhang; Qiaomei Yang; Rusen Zhou; Yan Xu; Pingping Gao; Yadong Zhao (Food Hydrocolloids, 2025)

Phytochemicals and their Nanoformulations for Overcoming Drug Resistance in Head and Neck Squamous Cell Carcinoma - Zhai Pingping; Chen Nan; Tang Yong (Pharmaceutical Research, 2025)

Water-in-water emulsions stabilized by konjac glucomannan/tragacanth gum hydrogels for riboflavin delivery - Nitong Bu; Huanglong Lin; Di Zhang; Xianrui Chen; Pingping Tan; Yuanbo Zhong; Liying Huang; Jie Pang; Lin Wang; Ruojun Mu (Journal of Food Engineering, 2025)

Reheating-induced gel properties change and flavor evolution of surimi-based seafood: Effects and mechanisms - Lingxiang Bao; Ruizhi Yang; Dieynabou Diao; Fang Tian; Yingyun Chen; Bin Zheng; Pingping Gao; Yadong Zhao (Food Chemistry, 2025)

Optimizing Strategy for Whole-Genome Genotype Imputation in Scallops - Yujue Wang; Ruixing Yao; Liang Zhao; Qianqian Zhang; Moli Li; Xiangfu Kong; Pingping Liu; Shanhuan Huang; Chen Hu; Zhenmin Bao; Xiaoli Hu (Aquaculture, 2025)

Consistent responses of the shrimp Litopenaeus vannamei gut microbiota to Enterocytozoon hepatopenaei infection across spatially distant farms - Shifeng Xu; Pingping Zhan; Jinquan Li; Jiong Chen; Qiongfen Qiu; Jinbo Xiong (Aquaculture, 2025)

Modification of salivary multilayer for improved oral lubrication - Pingping Tan; Huanglong Lin; Yuanbo Zhong; Jianshe Chen; Ruojun Mu (Trends in Food Science & Technology, 2025)

Response characteristics of soil Cd availability to microbes in paddy soil with long-term fertilization and its impact on Cd uptake in rice - Shuai Yuan; Pingping Chen; Wenxin Zhou; Hongmei Liu; Kaikai Cheng; Xiaoping Xiao; Haiming Tang; Zhenxie Yi (Science of The Total Environment, 2024)

Cu-Co binary metal-organic framework nanosheets for highly efficient degradation of norfloxacin using the Fenton-like process - Long Zhou; Houying Yuan; Hui Li; Songhua Chen; Pingping Zhao; Ruiming Zhang; Zeyang Lu; Zuliang Chen (Journal of Environmental Chemical Engineering, 2024)

PI3KR1 and AKT1 in largemouth bass (Micropterus salmoides): molecular cloning, characterization, and its involvement in the alleviation of hepatic glycogen deposition caused by insulin inclusion in vitro - Yuru Li; Shiwen Chen; Yijun Liu; Pingping Liu; Songlin Li; Ning Liu (Fish Physiology and Biochemistry, 2024)

Characterizing the uncertainty of CMORPH products for estimating orographic precipitation over Northern California - Zhe Li; Haonan Chen; Robert Cifelli; Pingping Xie; Xiaodong Chen (Journal of Hydrology, 2024)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Comparisons of stripe rust response, grain yield and quality between fungicide sprayed and non-sprayed treatments for newly developed wheat lines carrying different genes for adult-plant resistance to stripe rust - Hao Chen; Liangqi Zhang; Chuanguang Ding; Yuqi Luo; Guoyun Jia; Junming Feng; Yuqi Wang; Binfan Si; Jianian Zhou; Xin Li; Kebing Huang; Suizhuang Yang; et al. (Crop Protection, 2024)

Exploring the environmental influences and community assembly processes of bacterioplankton in a subtropical coastal system: Insights from the Beibu Gulf in China - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Yusen Li; Wenjian Chen; Zelong Zhao; Linyuan Jiang; Lei Zhou (Environmental Research, 2024)

Response of Cigar Tobacco (Nicotiana tabacum L.) Varieties to Low Potassium Stress and Dissecting Biochemical Determinants of Low Potassium Tolerance Mechanism - Xinying Chen; Pingping Wang; Suiling Ai; Naheeda Begum; Dezhi Kong; Hojat Asadollahpour Nanaei; Munib Ahmad; Shaista Jabeen; Lixin Zhang (Journal of Crop Health, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Seasonal dynamics of antibiotic resistance genes and mobile genetic elements in a subtropical coastal ecosystem: Implications for environmental health risks - Jinxia Peng; Dapeng Wang; Pingping He; Pinyuan Wei; Li Zhang; Wenlu Lan; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Wei Li; Yusi Zheng; Yusen Li; et al. (Environmental Research, 2024)

Non-intrusive load monitoring based on MoCo_v2, time series self-supervised learning - Tie Chen; Jiaqi Gao; Yimin Yuan; Shinan Guo; Pingping Yang (Energy and Buildings, 2024)

A novel yeast-based biosensor for the quick determination of Deoxynivalenol - Han Yang; Lianqun Du; Lu Geng; Xiao Liu; Zehua Xu; Ruonan Liu; Wentao Liu; Hu Zuo; Zongfen Chen; Xinyang Wang; Pingping Zhang; Tieqiang Sun (Analytica Chimica Acta, 2024)

Corrigendum to “Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus” [Veterin. Microbiol. 276 (2023) 109615] - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2024)

Fatty acids metabolism in ozone-induced pulmonary inflammatory injury: Evidence, mechanism and prevention - Mengyuan Li; Xiangbing Kong; Xiaotong Jian; Yacong Bo; Xinyi Miao; Huaiyong Chen; Pingping Shang; Xiaolei Zhou; Ling Wang; Qiao Zhang; Qihong Deng; Yuan Xue; et al. (Science of The Total Environment, 2024)

Transcriptome and metabolome analysis reveal key genes and metabolic pathway responses in Leersia hexandra Swartz under Cr and Ni co-stress - Yuexin Fu; Yi Lin; Zhenliang Deng; Mouyixing Chen; Guo Yu; Pingping Jiang; Xuehong Zhang; Jie Liu; Xuemeng Yang (Journal of Hazardous Materials, 2024)

Association Between Circulating Zinc Levels and Risk Factors of Metabolic Syndrome: Insights from a Bi-directional Mendelian Randomization Analysis and Cross-Sectional Study - Yuanyuan Wu; Guoqiong Xu; Ruixue Bai; Pingping Yu; Zhongxiang He; Mengxue Chen; Yukun Hu; Tao Jiang; Yuanhang Yang; Dongfang Liu; Ying Mei; Xiaoya Qi; et al. (Biological Trace Element Research, 2024)

miR397 regulates cadmium stress response by coordinating lignin polymerization in the root exodermis in Kandelia obovata - Chenglang Pan; Mingxiong Zhang; Jianming Chen; Haoliang Lu; Xuemei Zhao; Xiaofeng Chen; Lu Wang; Pingping Guo; Shuyu Liu (Journal of Hazardous Materials, 2024)

NIR-photocatalytic LDHB-mimetic CuS@ZnS nanoenzyme regulates arthritis microenvironment through lactate oxidation and hydrogen evolution - Dezhi Lu; Fan Wu; Kangming Chen; Wentao Li; Pingping Zhang; Yutong Hou; Yingze Su; Weixi Liu; Tianchang Wang; Yihao Liu; Chenglan Huang; Shuo Chen; et al. (Chemical Engineering Journal, 2024)

Sarafloxacin hydrochloride exposure disrupts gut microbiota and increases shrimp susceptibility to Vibrio anguillarum infection - Haonan Sha; Tingting Song; Pingping Zhan; Xinxu Zhang; Jiong Chen; Jinbo Xiong (Aquaculture, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

Sulforaphane inhibits the migration and invasion of BPDE-induced lung adenocarcinoma cells by regulating NLRP12 - Wei Wang; Shufan Chang; Xi He; XiaoLei Zhou; Pingping Shang; Yusong Chen; Xiaoke Wang; Lijuan Chen; Qiao Zhang; Yahong Qiao; Feifei Feng (Toxicology and Applied Pharmacology, 2024)

Aromatic acids affect the performances of constructed rapid infiltration systems based on red mud and coke: Removal efficiency, electron transport, and metabolism - Shengtao Liu; Pingping Lu; Yunnan Zhang; Shu Gao; Xinjuan Li; Menglin Chen; Yuxiang Lu; Chengyuan Su (Journal of Environmental Chemical Engineering, 2024)

Mechanistic insights into the adsorption and extraction of rare earth ions using oxygen- and phosphorus-doped porous graphitic carbon nitride - Yiping Feng; Pingping Chen; Xingye Lian; Chenyi He; Chaoyu Zheng; Haijian Lu; Longyong Lin; Guoguang Liu; Yirong Deng (Journal of Environmental Chemical Engineering, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

In-situ synthesis of ZIF-8 on magnetic pineapple leaf biochar as an efficient and reusable adsorbent for methylene blue removal from wastewater - Xiaoxiao Ma; Yutong Li; Yile Du; Shuangli Chen; Yunfan Bai; Lin Li; Chuhua Qi; Pingping Wu; Sijing Zhang (Environmental Science and Pollution Research, 2024)

Physiological-biochemical responses and transcriptomic analysis reveal the effects and mechanisms of sulfamethoxazole on the carbon fixation function of Chlorella pyrenoidosa - Yuhao Zhou; Yujiao Yue; Xinyang Chen; Feifan Wu; Wei Li; Pingping Li; Jiangang Han (Science of The Total Environment, 2024)

Assessing the impact of Chlorantraniliprole (CAP) pesticide stress on oilseed rape (Brassia campestris L.): Residue dynamics, enzyme activities, and metabolite profiling - Hui Zhang; Pingping Wang; Jiangfei Wang; Huijun Liu; Xiangning Chen (Pesticide Biochemistry and Physiology, 2024)

Physiological and biochemical responses of Leersia hexandra Swartz to nickel stress: Insights into antioxidant defense mechanisms and metal detoxification strategies - Mouyixing Chen; Pingping Jiang; Xuehong Zhang; Geoffrey I. Sunahara; Jie Liu; Guo Yu (Journal of Hazardous Materials, 2024)

Industrializable and pH-tolerant electropositive imidazolium chloride polymer for high-efficiency removal of perfluoroalkyl carboxylic acids from aqueous solution - Xiaohui Wei; Pingping Liu; Danyang Bai; Luyuan Zhang; Hongyan Mao; Wenjing Zhang; Tianqi Chen; Dan Yin; Tianhua Sun; Yanhao Zhang; Wenfen Zhang (Journal of Hazardous Materials, 2024)

N-nitrosodimethylamine exposure to zebrafish embryos/larvae causes cardiac and spinal developmental toxicity - Xiaoyi Liu; Jinge Song; Xiaotao Yan; Pingping Li; Jinhua Zhang; Bin Wang; Jing Si; Yong Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Accumulated Endogenous Abscisic Acid Contributes to the Cold Tolerance of Pre-planted Cultivated Tobacco - Qiansi Chen; Pingping Liu; Zefeng Li; Qingxia Zheng; Huina Zhou; Jinyan Liu; Peijian Cao; Ming Fang (Plant Molecular Biology Reporter, 2024)

Lateral Response Evaluation of Existing Pile by Adjacent Pile Driving in Claye Slope - Zhilin Wu; Pingping Rao; Jifei Cui; Qingsheng Chen; Sanjay Nimbalkar (Geotechnical and Geological Engineering, 2024)

Cd-contaminated soil remediation using MgFe2O4/chitosan carbon aerogel beads - Yutong Li; Xiaoxiao Ma; Yile Du; Shuangli Chen; Pingping Wu; Sijing Zhang (Journal of Environmental Chemical Engineering, 2024)

Fault diagnosis of spent fuel shearing machines based on improved residual network - Wang Pingping; Chen Jiahua (Annals of Nuclear Energy, 2024)

Effects of dietary supplementation with Radix Isatidis polysaccharide on egg quality, immune function, and intestinal health in hens - Panpan Shi; Zenghao Yan; Miaofen Chen; Pingping Li; Deqin Wang; Junjuan Zhou; Zhaojie Wang; Shihao Yang; Zhikun Zhang; Chuyuan Li; Yulong Yin; Peng Huang (Research in Veterinary Science, 2024)

Multi-objective decision-making for green infrastructure planning: Impacts of rainfall characteristics and infrastructure configuration - Wenjie Chen; Weiqi Wang; Chao Mei; Yisi Chen; Pingping Zhang; Peitong Cong (Journal of Hydrology, 2024)

Environmental investment timing and dual government incentives under uncertain carbon allowances - Jian Pan; Qingchun Meng; Pingping Chen; Yumei Jiang; Zhenfang Zhong (Journal of Cleaner Production, 2024)

Increase in iron-bound organic carbon content under simulated sea-level rise: A “marsh organ” field experiment - Dehong Hu; Wenjing Lan; Min Luo; Tianning Fan; Xin Chen; Ji Tan; Shihua Li; Pingping Guo; Jiafang Huang (Soil Biology and Biochemistry, 2023)

Response differences of gut microbiota in oligofructose and inulin are determined by the initial gut Bacteroides/Bifidobacterium ratios - Pingping Yin; Ting Du; Shanrong Yi; Chengcheng Zhang; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Research International, 2023)

Improving Wind Forecasts Using a Gale-Aware Deep Attention Network - Keran Chen; Yuan Zhou; Ping Wang; Pingping Wang; Xiaojun Yang; Nan Zhang; Di Wang (Journal of Meteorological Research, 2023)

Quantitative assessment of spatiotemporal dynamics in vegetation NPP, NEP and carbon sink capacity in the Weihe River Basin from 2001 to 2020 - Jiqiang Lyu; Xianghang Fu; Chen Lu; Yueyan Zhang; Pingping Luo; Peng Guo; Aidi Huo; Meimei Zhou (Journal of Cleaner Production, 2023)

Dissecting the genetic basis of grain weight and size in common oat by genome-wide association study - Honghai Yan; Di Deng; Pingping Zhou; Yun Peng; Xiaolong Dong; Shuchang Li; Yongjie Zhang; Qin Man; Ziqin Lv; Tao Chen; Changzhong Ren; Yuanying Peng (Journal of Cereal Science, 2023)

High titer (>200 g/L) lactic acid production from undetoxified pretreated corn stover - Yuwei Zhang; Zhaoxian Xu; Minrui Lu; Xingwang Ma; Sitong Chen; Yanchen Wang; Wenyuan Shen; Pingping Li; Mingjie Jin (Bioresource Technology, 2023)

Hyperspectral images classification of small sample based on the strategy of sample enlargement by superpixel pair method - Xueying Li; Pingping Fan; Zongmin Li; Huimin Qiu; Guangli Hou; Guangyuan Chen; Guoxing Ren (International Journal of Remote Sensing, 2023)

Microplastic aging alters the adsorption-desorption behaviors of sulfamethoxazole in marine animals: A study in simulated biological liquids - Jiaxuan Li; Yunxue Li; Bushra Maryam; Xiaochen Chen; Yanping Zong; Jianbo Tu; Pingping Zhang; Xianhua Liu (Marine Pollution Bulletin, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Incorporation of ascorbic acid and L-cysteine in sodium carboxymethyl cellulose coating delays color deterioration and extends the shelf-life of fresh-cut asparagus lettuce (Lactuca sativa var. angustata) - Renying Yu; Huibo Song; Yanan Chen; Nan Shi; Hui Shen; Pingping Shi; Huosheng Shu; Xiaoxue Kong; Lijuan Yu; Haibo Luo (Postharvest Biology and Technology, 2023)

Developing of CuxSnSO@GO aerogels used as highly efficient catalysts for cellulose transform to lactic acid under the synergy of Cu-Sn thermocatalysis and photocatalysis processes - Shaocong Yang; Zhen Wang; Pingping Li; Xinrui Wang; Liangyu Li; Chang Geun Yoo; Guihua Yang; Jiachuan Chen; Gaojin Lyu (Chemical Engineering Journal, 2023)

Realization of highly deformable freestanding borophene hybrid film for flexible energy storage device - Jiali Yu; Zhimin Fan; Fei Yu; Hang Zhao; Pingping Yao; Shengnan Chen; Haiyan Yang; Caizhen Zhu; Jian Xu (Chemical Engineering Journal, 2023)

Incorporating biotic phosphorus-acquisition strategies into soil phosphorus transformation under long-term salinization in a tidal wetland - Tianning Fan; Min Luo; Ji Tan; Dehong Hu; Xin Chen; Jiafang Huang; Shihua Li; Pingping Guo; Ji Chen (CATENA, 2023)

Soil carbon content prediction using multi-source data feature fusion of deep learning based on spectral and hyperspectral images - Xueying Li; Zongmin Li; Huimin Qiu; Guangyuan Chen; Pingping Fan (Chemosphere, 2023)

Meta-analysis reveals different functional characteristics of human gut Bifidobacteria associated with habitual diet - Pingping Yin; Chengcheng Zhang; Ting Du; Shanrong Yi; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Research International, 2023)

Above management: Scale development and empirical testing for public opinion monitoring of marine pollution - Jihong Chen; Pingping Li; Xue Wang; Kui Yi (Marine Pollution Bulletin, 2023)

Photocatalysis enhanced constructed wetlands effectively remove antibiotic resistance genes from domestic wastewater - Pingping Chen; Xiaofei Yu; Jingyao Zhang (Chemosphere, 2023)

Hydromechanical Modeling of High-Voltage Electropulse-Assisted Fluid Injection for Rock Fracturing - Peihao Ouyang; Pingping Rao; Jian Wu; Jifei Cui; Sanjay Nimbalkar; Qingsheng Chen (Rock Mechanics and Rock Engineering, 2023)

Plant above-ground biomass and litter quality drive soil microbial metabolic limitations during vegetation restoration of subtropical forests - Shuo Zhang; Ying-Ping Wang; Xi Fang; Jinlei Chen; Nannan Cao; Pingping Xu; Mengxiao Yu; Xin Xiong; Xiangping Tan; Qi Deng; Junhua Yan (Soil Ecology Letters, 2023)

Secukinumab plays a synergistic role with starvation therapy in promoting autophagic cell death of hepatocellular carcinoma via inhibiting IL-17A-increased BCL2 level - Rong Tang; Linmei Zheng; Jinfang Zheng; Jincai Wu; Pingping Chen; Jiacheng Chen; Dafeng Xu; Yongchao Zeng; Qijin Li; Zhensheng Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Evaluation of Cd2+ stress on Synechocystis sp. PCC6803 based on single-cell elemental accumulation and algal toxicological response - Yao Tao; Man He; Beibei Chen; Gang Ruan; Pingping Xu; Yixue Xia; Gaofei Song; Yonghong Bi; Bin Hu (Aquatic Toxicology, 2023)

Integration of nitrogen-doped carbon dots onto active layer of forward osmosis membrane for highly efficient antibacteria and enhanced membrane performances - Wen-Sheng Zou; Pingping Wu; Bihua Xiao; Xia Chen; Weili Kong; Yaru Li; Zhaoming Liu; Yaqin Wang (Journal of Environmental Chemical Engineering, 2023)

Carbon amendment rather than nitrate fertilization dominated the reassembly of the total, denitrifying, and DNRA bacterial community in the anaerobic subsoil - Chen Chen; Pingping Liu; Yingjie Liu; Yuquan Wei; Ji Li; Guo-chun Ding (Journal of Soils and Sediments, 2023)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Changes in bacterial diversity, co-occurrence pattern, and potential pathogens following digestate fertilization: Extending pathogen management to field for anaerobic digestion of livestock manure - Jingyang Gong; Baojun Liu; Pingping Liu; Lina Zhang; Chen Chen; Yuquan Wei; Ji Li; Guo-chun Ding (Waste Management, 2023)

Insights into carbon loss reduction during aerobic composting of organic solid waste: A meta-analysis and comprehensive literature review - Pingping Ye; Linfa Fang; Dan Song; Muyuan Zhang; Ronghua Li; Mukesh Kumar Awasthi; Zengqiang Zhang; Ran Xiao; Xinping Chen (Science of The Total Environment, 2023)

EST-SSR development and genetic diversity in the medicinal plant Pseudostellaria heterophylla (Miq.) Pax - Liyi Xu; Pingping Li; Jingjing Su; Ding Wang; Yunbo Kuang; Zuyun Ye; Meixia Chen (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Effects of different dry heating temperatures on the spatial structure and amino acid residue side-chain oxidative modification of soybean isolated proteins - Pingping Wen; Chao Xia; Lan Zhang; Yijing Chen; Huiqing Xu; Guiyou Cui; Jun Wang (Food Chemistry, 2023)

A new method for the determination of imidazole-like brown carbons using gas chromatography-mass spectrometry - Pingping Chen; Qinhao Lin; Taicheng An (Atmospheric Pollution Research, 2023)

The PER3rs772027021 SNP induces pigmentation phenotypes of dyschromatosis universalis hereditaria - Hongyu Chen; Pingping Yang; Dan Yang; Dongsheng Wang; Mao Lu; Yadong Li; Zhiqiang Zhong; Jing Zhang; Zhen Zeng; Zhi Liu; Xiaohua Zeng; Xu Jia; et al. (Journal of Molecular Medicine, 2023)

Effects of different levels of dietary chlorogenic acid supplementation on growth performance, intestinal integrity, and antioxidant status of broiler chickens at an early age - Wenhan Liu; Pingping Zha; Lili Guo; Yueping Chen; Yanmin Zhou (Animal Feed Science and Technology, 2023)

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Integrated transcriptome and metabolome analysis reveals the mechanism of tolerance to manganese and cadmium toxicity in the Mn/Cd hyperaccumulator Celosia argentea Linn - Guo Yu; Habib Ullah; Xinshuai Wang; Jie Liu; Baoliang Chen; Pingping Jiang; Hua Lin; Geoffrey I. Sunahara; Shaohong You; Xuehong Zhang; Asfandyar Shahab (Journal of Hazardous Materials, 2023)

Significant tipping points of sediment microeukaryotes forewarn increasing antibiotic pollution - Chaohua Wang; Zhiyuan Yao; Pingping Zhan; Xianghua Yi; Jiong Chen; Jinbo Xiong (Journal of Environmental Sciences, 2023)

Anti-inflammatory effects of extracellular vesicles from Morchella on LPS-stimulated RAW264.7 cells via the ROS-mediated p38 MAPK signaling pathway - Qi Chen; Chengchuan Che; Shanshan Yang; Pingping Ding; Meiru Si; Ge Yang (Molecular and Cellular Biochemistry, 2023)
Morchella is a kind of important edible and medicinal fungi, which is rich in polysaccharides, enzymes, fatty acids, amino acids and other active components. Extracellular vesicles (EVs) have a typical membrane structure, and the vesicles contain some specific lipids, miRNAs and proteins, and their can deliver the contents to different cells to change their functions. The present study investigated whether Morchella produce extracellular vesicles and its anti-inflammatory effect on lipopolysaccharide (LPS)-induced RAW246.7 macrophages. The experimental results showed that Morchella produced extracellular vesicles and significantly reduced the production of nitric oxide (NO) and reactive oxygen species (ROS) in a model of LPS-induced inflammation. In addition, the expression of inflammatory factor-related genes such as inducible nitric oxide synthase (iNOS), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and cyclooxygenase-2 (COX-2) showed dose-dependent inhibition. Morchella extracellular vesicles also can inhibit the inflammatory response induced by LPS by inhibiting the production of ROS and reducing the phosphorylation levels of the p38 MAPK signaling pathway. These results indicate that the Morchella extracellular vesicles can be used as a potential anti-inflammatory substance in the treatment of inflammatory diseases.

Effects of nutrient deficiency on the branch phenotype of the macroalgae Gracilariopsis lemaneiformis (Rhodophyta) - Pingping Li; Haihong Chen; Jingyu Zhang; Xiaoqing Feng; Baoheng Xiao; Yiyi Hu; Zhenghong Sui (Aquaculture, 2023)

Synergistic HA and NS mutations enhanced the virulence of a mouse-adapted H1N1 influenza A virus - Min Zhu; Jianqiao He; Hao Zeng; Pingping Wang; Yaohui Zhu; Fanyuan Sun; Xin Huang; Yi Xu; Chongqiang Huang; Jiancai Chen; Xinyi Guo; Huabo Zhou; et al. (Veterinary Microbiology, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

What happens to gut microorganisms and potential repair mechanisms when meet heavy metal(loid)s - Xiaoyi Liu; Jinhua Zhang; Jing Si; Pingping Li; Haining Gao; Weikun Li; Yong Chen (Environmental Pollution, 2023)

Assessment of heavy metals contamination and human health risk assessment of the commonly consumed medicinal herbs in China - Haiping Liu; Jianfeng Tang; Tongjun Chen; Pingping Zhu; Dongdong Sun; Weiyun Wang (Environmental Science and Pollution Research, 2023)

Transcriptomes of Different Tissues for Expression Characteristics Analysis of MYB gene Family in Kenaf (Hibiscus cannabinus L.) - Hu Li; Xin Yang; Sylvain Niyitanga; Qinyao He; Siyuan Chen; Jiantang Xu; Jianmin Qi; Aifen Tao; Pingping Fang; Liwu Zhang (Tropical Plant Biology, 2022)

Ploidy Identification by Flow Cytometry and Application of the Method to Characterize Seasonal Ploidy Variation of Wild Populations of the Red Alga Gracilariopsis lemaneiformis - Xiaoqing Feng; Haihong Chen; Baoheng Xiao; Qiong Wu; Jingyu Zhang; Ni Zhang; Pingping Li; Lu Wang; Jingru Yin; Zhenghong Sui (Marine Biotechnology, 2022)

BiPO4-coated carbon microtube electrodes: preparation and characterization of their properties and electrocatalytic degradation of methylene blue - Wenli Qin; Zefei Chen; Xueya Liu; Xinyi Zhang; Manqing Ai; Pingping Zhang; Ying Ye; Zengling Ma (Environmental Science and Pollution Research, 2022)

Identification and Characterization of microRNAs in the Gonads of Litopenaeus vannamei Using High-Throughput Sequencing - Wei Li; Pingping He; Xingzhi Zhang; Junliang Guan; Yongxian Chen; Li Zhang; Bin Zhang; Yusi Zheng; Xin Li; Qingsong He; Longcheng Liu; Chang Yuan; et al. (Fishes, 2022)
Although the expression of miRNAs has been widely applied to investigate on gonads, the role of miRNAs in the gonadal development of white Pacific shrimp (Litopenaeus vannamei) remains unknown. In this study, we performed high-throughput sequencing to identify the sex-related microRNAs (miRNAs) that elucidated the regulatory mechanisms on the gonadal differentiation of L. vannamei. We obtained a total of 29,671,557 and 28,526,942 raw reads from the ovaries and testes library, respectively. We then mapped 26,365,828 (92.73%) of the ovarian clean sequences and 23,694,294 (85.65%) of the testicular clean sequences for a transcriptome reference sequence of L. vannamei. After blasting the miRNA sequences against the miRBase database, we identified 153 significantly differentially expressed miRNAs between the ovaries and testes. To confirm the high-throughput sequencing results, we used a reverse transcriptase–quantitative polymerase chain reaction (RT-qPCR) to verify the expression patterns of the seven most differentially expressed miRNAs (i.e., novel_mir23, miR-92b-3p_3, miR-12-5p_2, novel_mir67, miR-279_1, let-7-5p_6, miR-263a-5p_1). According to the results of RT-qPCR, most of the miRNAs were expressed consistently with the high-throughput sequencing results. In addition, the target genes significantly enriched several Kyoto Encyclopedia of Genes and Genome (KEGG) pathways that were closely related to gonadal differentiation and development, including extracellular matrix–receptor interaction, Hedgehog signaling pathway, protein digestion and absorption and cell adhesion molecules (CAMs). This study revealed the first miRNAs sequencing of L. vannamei gonads. We identified sex-related differentially expressed miRNAs and KEGG pathways, which will be helpful to facilitate future research into the regulatory mechanism on the gonadal differentiation of L. vannamei.

Role of coke media strategy in an adsorption-biological coupling technology for wastewater treatment performance, microbial community, and metabolic pathways features - Chengyuan Su; Xibing Zhou; Pingping Lu; Xiaoyun Dai; Zhuxin Chen; Bocai Liang; Yihao Tian; Menglin Chen (Environmental Science and Pollution Research, 2022)

rtcisE2F promotes the self-renewal and metastasis of liver tumor-initiating cells via N6-methyladenosine-dependent E2F3/E2F6 mRNA stability - Zhenzhen Chen; Lan Huang; Kaili Wang; Lulu Zhang; Xiang Zhong; Zhongyi Yan; Benyu Liu; Pingping Zhu (Science China Life Sciences, 2022)

Cellular Heterogeneity Facilitates the Functional Differences Between Hair Follicle Dermal Sheath Cells and Dermal Papilla Cells: A New Classification System for Mesenchymal Cells within the Hair Follicle Niche - Yuyang Gan; Hailin Wang; Lijuan Du; Kaitao Li; Qian Qu; Weiwen Liu; Pingping Sun; Zhexiang Fan; Jin Wang; Ruosi Chen; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2022)

Dexmedetomidine post-conditioning alleviates myocardial ischemia–reperfusion injury in rats by ferroptosis inhibition via SLC7A11/GPX4 axis activation - Peng Yu; Jing Zhang; Yi Ding; Dandan Chen; Haijian Sun; Fenglai Yuan; Siyuan Li; Xiaozhong Li; Pingping Yang; Linghua Fu; Shuchun Yu; Jiru Zhang (Human Cell, 2022)

Finite Element Analysis of Electro-Thermal Coupling of Sandstone Under Lightning Currents - Pingping Rao; Yuanbing Xiang; Peihao Ouyang; Sanjay Nimbalkar; Qingsheng Chen (Geotechnical and Geological Engineering, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Biocompatibility of marine magnetotactic ovoid strain MO-1 for in vivo application - Changyou Chen; Pingping Wang; Long-Fei Wu; Tao Song (Journal of Oceanology and Limnology, 2021)

Causal associations of waist circumference and waist-to-hip ratio with type II diabetes mellitus: new evidence from Mendelian randomization - Kexin Li; Tianyu Feng; Lijuan Wang; Yang Chen; Pingping Zheng; Pan Pan; Min Wang; Isaac T. S. Binnay; Yingshuang Wang; Ruiyu Chai; Siyu Liu; Bo Li; et al. (Molecular Genetics and Genomics, 2021)

LRP10 Mutations May Correlate with Sporadic Parkinson’s Disease in China - Quanzhen Zhao; Pingping Ning; Xinglong Yang; Changhe Shi; Yuming Xu; Qiuyan Shen; Hongyan Huang; Dan Xie; Yalan Chen; Yanming Xu (Molecular Neurobiology, 2021)

PD-1 expression is elevated in monocytes from hepatocellular carcinoma patients and contributes to CD8 T cell suppression - Jin Yun; Genhua Yu; Pingping Hu; Yang Chao; Xingyu Li; Xiaobo Chen; Qichun Wei; Junfeng Wang (Immunologic Research, 2020)

Perfluoroalkyl substances in the Lingang hybrid constructed wetland, Tianjin, China: occurrence, distribution characteristics, and ecological risks - Ziang Chen; Gengbo Ren; Xiaodong Ma; Ye Ding; Yunmin Hui; Pingping Qin; Zhuoqi Xu; Xiujun Gu; Fang Yuan; Yanhai Liu (Environmental Science and Pollution Research, 2020)

Benzophenanthridine alkaloids suppress lung adenocarcinoma by blocking TMEM16A Ca2+-activated Cl− channels - Gaohua Zhang; Lin Zhu; Yucong Xue; Zhijun Zhao; Honglin Li; Zhiyun Niu; Xiangchong Wang; Pingping Chen; Jianping Zhang; Xuan Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Interaction of Mn and Cd during their uptake in Celosia argentea differs between hydroponic and soil systems - Jie Liu; Guo Yu; Pingping Jiang; Xingfeng Zhang; Dejia Meng; Zhe Chen; Alan J. M. Baker; Rongliang Qiu (Plant and Soil, 2020)

Local environmental selection and lineage admixture act as significant mechanisms in the adaptation of the widespread East Asian pond skater Gerris latiabdominis to heterogeneous landscapes - Zhen Ye; Juanjuan Yuan; Yahui Zhen; Jakob Damgaard; Kazutaka Yamada; Xiuxiu Zhu; Kun Jiang; Xin Yang; Wenwu Wang; Shujing Wang; Jingyu Liang; Siying Fu; et al. (Journal of Biogeography, 2020)
Aim Local environmental selection and lineage admixture have long been accepted as important adaptive mechanisms in adjusting widespread taxa to new environments. We studied a pond skater, Gerris latiabdominis , to explore the relative roles played by these two mechanisms in its process of adaptation to heterogeneous landscapes. Location East Asia. Taxon Gerris latiabdominis Miyamoto, 1958. Methods Mitochondrial (COI, COII) and nuclear (ddRAD‐seq) markers were sequenced from 202 individuals. Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. The demographical history was simulated by approximate Bayesian computation (ABC). The single‐nucleotide polymorphisms (SNPs) that may have been subjected to natural divergent selection among the populations were assessed, and the recent migration rates were estimated. Finally, shifts in suitable habitat from the last interglacial (LIG) to the present were predicted through ecological niche modelling (ENM). Results We found population structures inferred from both mitochondrial and nuclear genomes to be almost coincident and to correspond to temporal or spatial heterogeneity. The early Pliocene splitting event between the northern (NO) and southeastern (SE) groups is consistent with the ‘arid belt hypothesis’, followed by local environmental selection. Approximate Bayesian computation and gene flow estimation strongly suggested that the southwestern (SW) groups originated from a lineage admixture event between the SE and western (WE) groups and subsequently underwent ongoing gene flow from the SE group during the Pleistocene. The mito‐nuclear discordance pattern in the SW group was probably due to the ancient mitochondrial differentiation. Main conclusion Our results suggest that both local environmental selection and lineage admixture acted as significant mechanisms of G. latiabdominis adaptation to heterogeneous landscapes in East Asia. Furthermore, this study showed that conclusions based exclusively on mitochondrial data might mislead taxonomic, phylogenetic and phylogeographical studies.

Alcohol inhibits morphine/cocaine reward memory acquisition and reconsolidation in rats - Shimin Zhu; Pingping Chen; Mingzhu Chen; Jiawei Ruan; Wanying Ren; Xinyu Zhang; Yang Gao; Yanqin Li (Psychopharmacology, 2020)

A cytokinin-activation enzyme-like gene improves grain yield under various field conditions in rice - Changgui Wang; Guokui Wang; Yang Gao; Guihua Lu; Jeffrey E. Habben; Guanfan Mao; Guangwu Chen; Jiantao Wang; Fan Yang; Xiaoqiang Zhao; Jing Zhang; Hua Mo; et al. (Plant Molecular Biology, 2020)

Characterization on the water deprivation-associated physiological traits as well as the related differential genes during seed filling stage in wheat (T. aestivum L.) - Yingjia Zhao; Pingping Du; Zijia Chen; Xinyang Bai; Ruize Lin; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

An effective method for identification of three mussel species and their hybrids based on SNPs - Xingqiang Chen; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song; Lei Liu; Ce Shi; Pingping Zhan (Conservation Genetics Resources, 2020)

Integrative taxonomy uncovers hidden species diversity in the rheophilic genus Potamometra (Hemiptera: Gerridae) - Chenguang Zheng; Zhen Ye; Xiuxiu Zhu; Haiguang Zhang; Xue Dong; Pingping Chen; Wenjun Bu (Zoologica Scripta, 2020)
The genus Potamometra Bianchi, 1896 represents big rheophilic semi‐aquatic bugs that typically inhabit middle‐altitude mountainous streams. Here, we integrated molecular and morphological data for delimiting species boundaries and understanding the evolutionary history of the genus Potamometra . Twenty‐seven complete mitochondrial genomes of Potamometra were sequenced, with samples representing most of the known geographically distributed locations around the Sichuan Basin. The results of different species delimitation methods (ABGD, bPTP, GMYC and BPP) based on the monolocus or multilocus data strongly supported the existence of two cryptic new species ( Potamometra anderseni Zheng, Ye & Bu, sp. nov. and Potamometra zhengi Zheng, Ye & Bu, sp. nov.) although more entities were found in the tree‐based delimitation methods. The two new species were successfully validated using morphological characters within a detailed taxonomic framework. Phylogenetic analyses supported the reciprocal monophyly of the seven highly node‐supported clades, which were matched with the five known species and two new taxa. A novel gene arrangement pattern that two trnF (trnF1 and trnF2) genes separated by an intergenic spacer (IGS) were found in all the species except the sister group of Potamometra berezowskii Bianchi, 1896 and Potamometra linnavuorii Chen, Nieser & Bu, 2016. This gene rearrangement event could be explained by the tandem duplication and random loss (TDRL) model. Our study emphasized that the combination of molecular sequence data, morphological characters and mitochondrial structural information could improve the accuracy of species delimitation.

Molecular identification reveals hybrids of Mytilus coruscus × Mytilus galloprovincialis in mussel hatcheries of China - Weijia Zhang; Ronghua Li; Xingqiang Chen; Chunlin Wang; Zhongqi Gu; Changkao Mu; Weiwei Song; Pingping Zhan; Ji Huang (Aquaculture International, 2020)

New Fractal Evidence of Pacific Plate Subduction in the Late Mesozoic, Great Xing’an Range, Northeast China - Pingping Zhu; Qiuming Cheng; Guoxiong Chen (Journal of Earth Science, 2019)

Early Cretaceous volcanic and sub-volcanic rocks in the Erlian Basin and adjacent areas, Northeast China: new geochemistry, geochronology and zircon Hf isotope constraints on petrogenesis and tectonic setting - Jianzhou Tang; Zhicheng Zhang; Zejia Ji; Yan Chen; Ke Li; Yang Jinfu; Pingping Liu (International Geology Review, 2019)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

Complement Complex C5b-9 Levels Are Associated with the Clinical Outcomes of Acute Ischemic Stroke and Carotid Plaque Stability - Weixin Si; Pingping He; Yi Wang; Yu Fu; Xin Li; Xiaoru Lin; Fenghua Chen; Guodong Cao; Hong Zhang (Translational Stroke Research, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Evolutionary and functional analyses of the 2-oxoglutarate-dependent dioxygenase genes involved in the flavonoid biosynthesis pathway in tobacco - Zhong Wang; Shanshan Wang; Mingzhu Wu; Zefeng Li; Pingping Liu; Feng Li; Qiansi Chen; Aiguo Yang; Jun Yang (Planta, 2019)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae) - Zhen Ye; Juanjuan Yuan; Min Li; Jakob Damgaard; Pingping Chen; Chenguang Zheng; Haibin Yu; Siying Fu; Wenjun Bu (Journal of Biogeography, 2018)
Aim Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis , to explore the relative roles played by these two factors in population genetic connectivity. Location Sichuan Basin, China. Methods Mitochondrial ( COI , COII , Cytb, 16S) and nuclear ( EF ‐1α, ITS 1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum ( LGM ) to the present were predicted through fine‐tuned ecological niche modelling ( ENM ). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated using beast . Finally, the least cost path ( LCP ) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot ( BSP ) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis , in global biodiversity hotspots is proposed and discussed in this paper.

Formulation and In Vitro Release Kinetics of Mucoadhesive Blend Gels Containing Matrine for Buccal Administration - Xiaojin Chen; Jun Yan; Shuying Yu; Pingping Wang (AAPS PharmSciTech, 2018)

Limit analysis approach for accessing stability of three-dimensional (3-D) slopes reinforced with piles - Pingping Rao; Linxue Zhao; Qingsheng Chen; Lin Li (Marine Georesources & Geotechnology, 2017)

Light irradiation helps magnetotactic bacteria eliminate intracellular reactive oxygen species - Kefeng Li; Pingping Wang; Chuanfang Chen; Changyou Chen; Lulu Li; Tao Song (Environmental Microbiology, 2017)
Summary Magnetotactic bacteria (MTB) demonstrate photoresponse. However, little is known about the biological significance of this behaviour. Magnetosomes exhibit peroxidase‐like activity and can scavenge reactive oxygen species (ROS). Magnetosomes extracted from the Magnetospirillum magneticum strain AMB‐1 show enhanced peroxidase‐like activity under illumination. The present study investigated the effects of light irradiation on nonmagnetic (without magnetosomes) and magnetic (with magnetosomes) AMB‐1 cells. Results showed that light irradiation did not affect the growth of nonmagnetic and magnetic cells but significantly increased magnetosome synthesis and reduced intracellular ROS level in magnetic cells. Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) was performed to analyse the expression level of magnetosome formation‐associated genes ( mamA , mms6 , mms13 and mmsF ) and stress‐related genes ( recA , oxyR , SOD , amb0664 and amb2684 ). Results showed that light irradiation upregulated the expression of mms6 , mms13 and mmsF . Furthermore, light irradiation upregulated the expression of stress‐related genes in nonmagnetic cells but downregulated them in magnetic cells. Additionally, magnetic cells exhibited stronger phototactic behaviour than nonmagnetic ones. These results suggested that light irradiation could heighten the ability of MTB to eliminate intracellular ROS and help them adapt to lighted environments. This phenomenon may be related to the enhanced peroxidase‐like activity of magnetosomes under light irradiation.

Vectorization of classified remote sensing raster data to establish topological relations among polygons - Bin Xu; Jianping Chen; Pingping Yu (Earth Science Informatics, 2017)

Differentiation of bone marrow stromal cells into schwann-like cells using dihydrotestosterone combined with a classical induction method - Xiaofan Yang; Jianghai Chen; Pingping Xue; Ranran Liu; Wei Ji; Xiaocheng Lu; Xin Liu; Zhenbing Chen (Biotechnology Letters, 2017)

Resveratrol Pretreatment Decreases Ischemic Injury and Improves Neurological Function Via Sonic Hedgehog Signaling After Stroke in Rats - Pingping Yu; Li Wang; Fanren Tang; Li Zeng; Luling Zhou; Xiaosong Song; Wei Jia; Jixiang Chen; Qin Yang (Molecular Neurobiology, 2017)

Degradation of triclosan in the presence of p-aminobenzoic acid under simulated sunlight irradiation - Pingping Zhai; Xuan Chen; Wenbo Dong; Hongjing Li; Jean-marc Chovelon (Environmental Science and Pollution Research, 2017)

Mechanical Testing of Tomato Plant Stem in Relation to Structural Composition - Xiliang Zhang; Qian Guo; Yunfeng Xu; Pingping Li; Cheng Chen; Shuo Wu (Agricultural Research, 2016)

Composition and distribution of planktonic ciliates in the southern South China Sea during late summer: Comparison between surface and 75 m deep layer - Huaxue Liu; Pingping Shen; Chunhou Li; Zuozhi Chen; Zhanhui Qi; Honghui Huang (Journal of Ocean University of China, 2016)

Cloning and functional analyses of pepper CaRKNR involved in Meloidogyne incognita resistance - Zhenchuan Mao; Pingping Zhu; Feng Liu; Yonghong Huang; Jian Ling; Guohua Chen; Yuhong Yang; Dongxin Feng; Bingyan Xie (Euphytica, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

BTG3 upregulation induces cell apoptosis and suppresses invasion in esophageal adenocarcinoma - Yuwen Du; Pingping Liu; Wenqiao Zang; Yuanyuan Wang; Xiaonan Chen; Min Li; Guoqiang Zhao (Molecular and Cellular Biochemistry, 2015)

The inhibitory effect of troglitazone on macrophage differentiation mediated by repressing NF-κB ctivation independently of PPARγ - Yongjun Chen; Zhiyuan Niu; Jun Cui; Pingping Shen (Molecular & Cellular Toxicology, 2014)

Molecular data and ecological niche modelling reveal the P leistocene history of a semi‐aquatic bug ( M icrovelia douglasi douglasi ) in E ast A sia - Zhen Ye; Gengping Zhu; Pingping Chen; Danli Zhang; Wenjun Bu (Molecular Ecology, 2014)
This study investigated the Pleistocene history of a semi‐aquatic bug, Microvelia douglasi douglasi Scott, 1874 (Hemiptera: Veliidae) in East Asia. We used M. douglasi douglasi as a model species to explore the effects of historical climatic fluctuations on montane semi‐aquatic invertebrate species. Two hypotheses were developed using ecological niche models ( ENMs ). First, we hypothesized that M. douglasi douglasi persisted in suitable habitats in southern Guizhou, southern Yunnan, Hainan, Taiwan and southeast China during the LIG . After that, the populations expanded (Hypothesis 1). As the spatial prediction in the LGM was significantly larger than in the LIG , we then hypothesized that the population expanded during the LIG to LGM transition (Hypothesis 2). We tested these hypotheses using mitochondrial data ( COI + COII ) and nuclear data ( ITS 1 + 5.8S+ ITS 2). Young lineages, relatively deep splits, lineage differentiation among mountain ranges in central, south and southwest China and high genetic diversities were observed in these suitable habitats. Evidence of mismatch distributions and neutrality tests indicate that a population expansion occurred in the late Pleistocene. The Bayesian skyline plot ( BSP ) revealed an unusual population expansion that likely happened during the cooling transition between LIG and LGM . The results of genetic data were mostly consistent with the spatial predictions from ENM , a finding that can profoundly improve phylogeographic research. The ecological requirements of M. douglasi douglasi , together with the geographical heterogeneity and climatic fluctuations of Pleistocene in East Asia, could have shaped this unusual demographic history. Our study contributes to our knowledge of semi‐aquatic bug/invertebrate responses to Pleistocene climatic fluctuations in East Asia.

Potential for forest vegetation carbon storage in Fujian Province, China, determined from forest inventories - Yin Ren; Xiaohua Wei; Li Zhang; Shenghui Cui; Feng Chen; Yongzhu Xiong; Pingping Xie (Plant and Soil, 2011)

Endogenous enkephalin does not contribute to the cerebral anti-hyperalgesic action of gabapentin - ShaoHui Chen; Jing Zhao; YuGuang Huang; AiLun Luo; PingPing Zuo; Nan Yang; WenYu Hao (Science China Life Sciences, 2010)

Some observations on harmful algal bloom (HAB) events along the coast of Guangdong, southern China in 1998 - Yuzao Qi; Jufang Chen; Zhaohui Wang; Ning Xu; Yan Wang; Pingping Shen; Songhui Lu; I.J. Hodgkiss (Hydrobiologia, 2004)